Hack the cybersecurity interview : a complete interview preparation guide for jumpstarting your cybersecurity career - Underhill, Ken; Foulon, Christophe; Hopkins, Tia (Packt Publishing Ltd., 2022)
Get your dream job and set off on the right path to achieving success in the cybersecurity field with expert tips on preparing for interviews, understanding cybersecurity roles, and more About This Audiobook Get well-versed with the interview process for cybersecurity job roles Prepare for SOC analyst, penetration tester, malware analyst, digital forensics analyst, CISO, and more roles Understand different key areas in each role and prepare for them In Detail This audiobook is a comprehensive guide that helps both entry-level and experienced cybersecurity professionals prepare for interviews in a wide variety of career areas. Complete with the authors' answers to different cybersecurity interview questions, this easy-to-follow and actionable audiobook will help you get ready and be confident. You'll learn how to prepare and form a winning strategy for job interviews. In addition to this, you'll also understand the most common technical and behavioral interview questions, learning from real cybersecurity professionals and executives with years of industry experience. By the end of this audiobook, you'll be able to apply the knowledge you've gained to confidently pass your next job interview and achieve success on your cybersecurity career path. Audience This cybersecurity audiobook is for college students, aspiring cybersecurity professionals, computer and software engineers, and anyone looking to prepare for a job interview for any cybersecurity role. The audiobook is also for experienced cybersecurity professionals who want to improve their technical and behavioral interview skills. Recruitment managers can also use this book to conduct interviews and tests.